Adjunctive Therapies to Cerclage for the Prevention of Preterm Birth: A Systematic Review - Emily A. DeFranco; Amy Miyoshi Valent; Tondra Newman; Jodi Regan; Jessica Smith; Louis J. Muglia (Obstetrics and Gynecology International)
The aim of this paper is to provide a thorough summary of published studies that have assessed the efficacy of adjunctive therapies used in addition to cervical cerclage as a preventive measure for preterm birth. We limited our paper to patients treated with cerclage plus an additional prophylactic therapy compared to a reference group of women with cerclage alone. The specific adjunctive therapies included in this systematic review are progesterone, reinforcing or second cerclage placement, tocolytics, antibiotics, bedrest, and pessary. We searched PubMed and Cochrane databases without date criteria with restriction to English language and human studies and performed additional bibliographic review of selected articles and identified 305 total studies for review. Of those, only 12 studies compared the use of an adjunctive therapy with cerclage to a reference group of cerclage alone. None of the 12 were prospective randomized clinical trials. No comparative studies were identified addressing the issues of antibiotics, bedrest, or pessary as adjunctive treatments to cerclage. None of the 12 studies included in this paper demonstrated a clear benefit of any adjunctive therapy used in addition to cerclage over and above cerclage used alone; however, few studies with small numbers limited the strength of the conclusions.